Social media and adapting social cohesiveness through 1Malaysia wireless village programme: a conceptual framework - Sahharon, Hamizah; Bolong, Jusang; Omar, Siti Zobidah; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (2014)
1Malaysia Wireless Village Programme is one of the efforts initiated by the Malaysian government to create an informative rural community. Such programme not only offers free internet access to create awareness to the use of the internet, but it also has a conceivable impact towards rural communities’ interpersonal relationship that is reflected through the adaptation of social cohesion. As suggested throughout this paper, a cohesive relationship is possible amid their social interactions via the functional building blocks of social media. The result of this paper will develop a tentative conceptual framework in which the relationship between functional building blocks of social media and adapting social cohesion through 1Malaysia Wireless Village Programme.